Transformasi Manajemen Pendidikan Islam Melalui Kepemimpinan Spiritual di Era Artificial Intelligence - Badrus Soleh; Isyrohil Muyassaroh (re-JIEM (Research Journal of Islamic Education Management), 2026)
The development of Artificial Intelligence (AI) is driving significant changes in Islamic education management, demanding efficiency and innovation, but also presenting challenges to spiritual and ethical values. This study aims to analyze the role of spiritual leadership in transforming Islamic education management in the AI era and formulate an integrative model based on technology and Islamic values. The study used a qualitative approach with a systematic literature observation design of reputable journal articles from the Scopus, Web of Science, Google Scholar, and SINTA databases. The study results indicate that spiritual leadership is the foundation for planning the ethical use of AI. The transformation model includes the integration of organizational vision and values, organizational culture, human resource competencies, and an AI-based management system as a framework for managing sustainable change